2013
DOI: 10.5625/lar.2013.29.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary high fat on prostate intraepithelial neoplasia in TRAMP mice

Abstract: Increased fat intake is known to be a major cause of prostate cancer. In this study, we investigated the effect of dietary high fat on prostate intraepithelial neoplasia using transgenic adenocarcinoma mouse prostate (TRAMP) mice. Six-week-old male TRAMP mice were fed AIN93G (control group, 4.0 kcal/kg, n=6) and AIN93G-HFD (experimental group, 4.8 kcal/kg, n=7) for 10 weeks. Prostate histopathology, urogenital tract (UGT) weight, epididymal white adipose tissue weight, argyrophilic nucleolar organizer regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
2
2
0
1
Order By: Relevance
“…We concluded that HFD could promote TRAMP mice PCa development and progression. Similar findings were reported by Llaverias et al [ 12 ], Bonorden et al [ 13 ], Park et al [ 14 ], and Chang et al [ 15 ]. Although emerging evidence revealed that HFD was closely related with PCa development and progression, no clear mechanism was uncovered yet.…”
Section: Introductionsupporting
confidence: 91%
“…We concluded that HFD could promote TRAMP mice PCa development and progression. Similar findings were reported by Llaverias et al [ 12 ], Bonorden et al [ 13 ], Park et al [ 14 ], and Chang et al [ 15 ]. Although emerging evidence revealed that HFD was closely related with PCa development and progression, no clear mechanism was uncovered yet.…”
Section: Introductionsupporting
confidence: 91%
“…TRAMP mice fed a Western diet (containing 21.2% fat and 0.2% cholesterol) for 20 weeks also show increased histopathological scores compared to those eating a chow diet (containing 4.5% fat and 0.002% cholesterol) . We previously reported that TRAMP mice fed a high‐fat (45% Kcal fat) diet produce consistent results compared to TRAMP mice fed a control (16% Kcal fat) diet when mice were fed each diet for 10 weeks . In the present study, the histopathological score increased with age and high‐fat diet consumption.…”
Section: Discussionsupporting
confidence: 74%
“…for example, the study by Wang et al showed that a low-fat diet decreased the tumor growth of xenografted lncaP cells (23). another study demonstrated that a high-fat diet induced a high level of serum leptin and high argyrophilic nucleolar organizer region (agnor) counts in a transgenic adenocarcinoma of mouse prostate (traMP) model (24). these studies suggested that chronic hyperleptinemia might be related to Pca progression.…”
Section: Discussionmentioning
confidence: 94%